PENERAPAN MULTIKULTURAL DALAM PELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM KONSEP BHINEKA TUNGGAL IKA DI SEKOLAH DASAR - Sihite, Dorawan Lia; Meha, Nurhabibah; Suaidah Lubis, Rifa Atul (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
Indonesia is a pluralistic country with a diversity of ethnicities, languages, religions and cultures. The diversity of the Indonesian nation can be seen from two perspectives, namely vertical and horizontal. There are many students who do not understand or understand how to respect fellow friends who are different from themselves so that the value of tolerance is almost extinct. This study aims to find out how a teacher can implement ways to help students become aware of this diversity. The method used is the Library Research method (literary study) where the Library Research method (library study) has benefits including: Exploring the basic theories and concepts that have been discovered by previous researchers. Following the development of research in the field to be studied. Gain a broader orientation on the chosen topic. The results of these findings are (1) Building an attitude of equality (2) Encouraging social substance (3) Building Gender Quality (4) Introducing the shape of traditional houses and traditional clothes from various ethnicities (5) Inviting students to taste food from various regions (6) Listening to folk songs (7) Showing different ways of dressing, both from ethnic groups.